Representations of Islam and Muslims in Media Addressed by Corpus-Based Approaches: Systematic Literature Review - Alluhaidah, Monther (International Journal of Linguistics and Translation Studies, 2023)
In the last decade, the synergy of corpus linguistics (CL) methods within critical discourse analysis (CDA) has gained increasing popularity. This study aims to review and analyse studies related to different representations of Islam and Muslims in mainstream and alternative media addressed by corpus methodologies. It seeks to identify cross-cutting themes, similarities and differences and offer a synthesis of the literature findings to map the research topics that covered Islam and Muslims in media. Research papers are systematically searched in Web of Science, Scopus, Google Scholar, IEEE Xplore, and Science Direct from 2000 to July 2021. A total of 8 articles are selected on the basis of inclusion and exclusion criteria. All these articles are incorporated coherently to answer four predetermined research questions. This systematic literature review results show that the studies focus to a great extent only on Islam as a religion only and Muslim women, not on other topics, that are discriminatorily portrayed in the western media. In terms of women’s representations, they are depicted as either passive victims or active fighters. Whereas Islam is represented relatively negatively as an ideology, not a religion, and they use the reduction and confirmation hypothesis by selecting news articles to justify a predetermined idea. Keywords: Corpus linguistics, Critical Discourse Analysis (CDA), Corpora, Islam and Muslims, newspaper discourse, media representation. Systematic Literature Review.